Heavy Equipment Rental Information System Development using the Prototyping Method - Fitrisia, Yuli; Owen, Marcel (Politeknik Negeri Batam, 2025)
A private company engaged in heavy equipment rental services, established on June 19, 2012, in Pekanbaru. In the current business process, customers who wish to rent heavy equipment or seek information about it can only do so during office hours, making the rental process less efficient. Record-keeping is still done using Excel, which increases the risk of data loss. Therefore, a solution has been proposed to develop a web-based information system to access and manage the process easily. The information system was developed using the prototyping method. The choice of the prototyping method is made to speed up development time, ease system completion, and avoid discrepancies between developers and users. The information system is then tested through Black Box testing and usability testing. From the Black Box testing results, it was found that the system's functionality for all users has been successfully implemented and operates as expected. Meanwhile, the usability testing results showed an average score of 89%, indicating that users strongly agree with the system's usability. This research helps to facilitate customers and administrators in the heavy equipment rental process by providing quick and easy access to information on prices, schedules, and equipment types, while also improving data recording to reduce the risk of data loss and facilitate administrative tasks.